Local Wisdom-Based Sustainable Tourism Village Development Collaboration in Badung Regency - Ni Luh Yulyana Dewi; Bambang Supriyono; Andy Fefta Wijaya; Siti Rochmah (GoAcademica Research & Publishing, 2023)
Tourism development aims to preserve nature, the environment and resources which are realized through the implementation of tourism development plans by taking into account the diversity, uniqueness and uniqueness of culture and nature, as well as human needs for tourism. This study used a qualitative design with a descriptive research type. In field research, researchers collect data using observation techniques, interviews, and document studies. The results of this study indicate that there are still gaps in the dynamics of collaborative governance in the development of sustainable tourism villages based on local wisdom in Badung Regency. This gap is due to data findings in the field that the government's role is still dominant and there are delays in transforming existing policies in regional action plans. This gap can be seen from the indicators of the success of the collaboration, namely based on institutional agreements which are characterized by limited joint commitments without being elaborated in depth in favor of each stakeholder and their performance achievements. In the process of developing a sustainable tourism village based on local wisdom to support tourism in Badung Regency, this can be done by issuing a policy by the government, by applying the Tri Hita Karana concept to ensure that all development is in accordance with its designation.